Garnish skills training for beginners of UKM Pondok Sarong Sumarni, Samarinda - Zuhriah, Zuhriah; Kadang, Tandi; Gunadi, Gunadi (Community Empowerment, 2021)
This community service aims to help UKM Pondok Sarong Sumarni, in stimulating and developing skills related to garnish skills training. This activity is carried out using training methods, both theoretically and practically. The community service showed that the participants had made garnishes, starting from the carving process to the presentation of dish decorations for food and drinks. These garnish skills can be an additional source of income for the community.